2015
DOI: 10.1248/bpb.b15-00096
|View full text |Cite
|
Sign up to set email alerts
|

Choose Delicately and Reuse Adequately: The Newly Revealed Process of Autophagy

Abstract: Autophagy is a degradation system for intracellular components. One of the roles of autophagy is the prompt removal of damaged organelles. Another unique role is to supply resources that maintain metabolism in response to the cellular nutritional state. Precise management of all the components in the autophagic system is essential for cellular health. Especially important are the selectivity of target cargos for autophagy, and the coordination of autophagy with the lysosomal catabolic process. This review outl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 61 publications
0
90
0
1
Order By: Relevance
“…It was hypothesized that a slight vacuolation may be present in the normal human placenta as a natural and physiological form of cell degradation which promotes survival. [20,21] Meng et al [2] found much more trophoblastic vacuoles in placentas of GDM compared to controls. [2] Hyperglycemia and hypoxia which have a role in the etiology of GDM may enhance the lysosome/vacuole functions of the trophoblasts, which result in widespread cytoplasmic vacuolation and altered transplacental metabolic exchange that may lead to cell death.…”
Section: Discussionmentioning
confidence: 98%
“…It was hypothesized that a slight vacuolation may be present in the normal human placenta as a natural and physiological form of cell degradation which promotes survival. [20,21] Meng et al [2] found much more trophoblastic vacuoles in placentas of GDM compared to controls. [2] Hyperglycemia and hypoxia which have a role in the etiology of GDM may enhance the lysosome/vacuole functions of the trophoblasts, which result in widespread cytoplasmic vacuolation and altered transplacental metabolic exchange that may lead to cell death.…”
Section: Discussionmentioning
confidence: 98%
“…Model building was performed with the cocrystal structure of human ATG4B with LC3 (1−120) as template (PDB code: 2Z0D) 12 using the following procedure: (1) in silico mutation of the TFG residues of LC3 into Z-FA(G)-FMK; (2) rebuilding of A280H using the structure 2Z0E 12 to reproduce the human sequence; (3) removal of the fluorine atom of Z-FA(G)-FMK and formation of a covalent bond between the sulfur atom of Cys74 and the reactive methylene unit of FMK. Here, the second, alternate conformation of the side chain of Cys74 in the crystal structure 2Z0D was used as this is closer to the FMK group.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…1 The hallmark of autophagy is the formation of autophagosomes and subsequent fusion with lysosomes to achieve degradation of their contents. Dysregulation of autophagy has been recently described in the pathogenesis of a variety of diseases such as cancer, neurodegenerative and metabolic disorders, and viral infections.…”
mentioning
confidence: 99%
“…Autophagy, also called self-eating, a natural and evolutionarily conserved lysosomal degradation and renovation process to hydrolyze unused or dysfunctional cellular components, such as long-lived or misfold proteins and useless organelles [23]. Actually, the basal autophagy activity is essential for cell homeostasis, involving cell growth, survival, development and death.…”
Section: Autophagy: a Brief Introductionmentioning
confidence: 99%
“…One common hallmark of autophagy is mediated by the multiple autophagy-related (Atg) genes and their associated enzymes. The main and most common pathway, macroautophagy, usually called autophagy, is an intracellular recycling system, used primarily to mediate bulk degradation of superfluous or damaged cytosolic materials [23]. This autophagy processes include several In the breakdown step, autophagic materials or contents are hydrolyzed by lysosomal enzymes in autolysosome.…”
Section: Autophagy: a Brief Introductionmentioning
confidence: 99%